EFFECTS OF ZINC, BORON AND ACTIVE DRY YEAST SPRAYS ON YIELD AND FRUIT QUALITY OF ZAGHLOUL DATE PALM - Mostafa, R.A. A. (Arab Universities Journal of Agricultural Sciences, 2015)
The beneficial effects of boron, zinc and active dry yeast on yield and fruit quality of Zaghloul date palm grown at the Experimental Orchard, Faculty of Agriculture, Assiut University, Egypt was studied during 2011, 2012 and 2013 seasons. The experiment was set up in a complete randomized block design with ten replicates each of one bunch. All treatments were sprayed two times after fruit set and one month later. The obtained results could be summarized as follow: -       Boron, zinc and active dry yeast sprays significantly increased the fruit retention percentage and bunch weight compared to the untreated ones. Yeast application was more effective compared with boron or zinc application. -       Spraying either yeast, boron or zinc at any studied concentration was accompanied with improving fruit quality in terms of significant increase in fruit weight, total soluble solids and sugar contents. No significant differences were detected between spraying with yeast at 250 or 500 ppm, 500 or 1000 ppm zinc, as well as, boron at 1000 or 2000 ppm. Moreover, active dry yeast spraying revealed the highest improvement in palm yield and fruit quality. However, it can be concluded that spraying either boric acid, zinc sulphate or active dry yeast twice after fruit set and one month later increased the palm yield and improved the fruit quality of Zaghloul date palm. Meanwhile, using dry yeast as more effective than both boric acid and zinc sulphate.